Unheard Voices of Customers Toward Services and Practices of Eastern Samar Electric Cooperative (Esamelco) - Jericho D. Ecija; John Austin Mendoza (Peerian Journals Publishing, 2021)
This phenomenological study was the enhancement of a certain scheme related to the CASR Thematic Way for continual improvisation on such experiences in Eastern Samar Electric Cooperative (SAMELCO) services, which can be an avenue to sustain great effort and, in some way, or another improve recognized practices. This paper could also require some future related research studies which can involve quantitative or mixed method or research when it comes of the services rendering by the electrical companies
Keywords: CASR; phenomenological; Thematic; continual